A review of the optimal allocation of distributed generation: Objectives, constraints, methods, and algorithms - Pesaran H.A M.; Huy P.D.; Ramachandaramurthy V.K. (Elsevier Ltd, 2023)
Circuit theory; Energy efficiency; Optimization; Dg siting; Dg sizings; Distributed generators; Distributed resources; Objective functions; Optimal allocation; Optimal DG allocation; Optimization algorithms; Distributed power generation